PENGARUH PENDIDIKAN KARAKTER TERHADAP MOTIVASI BERPRESTASI PADA SISWA MADRASAH ALIYAH BOARDING SCHOOL PROVINSI ACEH - Mukhlis; Sari Rizki (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
In principle, the character education carried out by the teacher/ustadz at the boarding school's state Islamic boarding school students can build the personal values ​​of each student, so that they become good citizens, namely; actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. This study aims to look at the dominant factors in the formation of character education and achievement motivation and to see the simultaneous influence of character education on achievement motivation. The methodology used in this study is a mix method using SEM analysis for quantitative data and editing for qualitative data, with data collection techniques in the form of questionnaires, interviews. The results showed that. 1). For the first aspect, partially the formation of character education is found through the discipline aspect, amounting to 0.79 or 79%, then followed by the hard work aspect (X3) of 0.715 or 71.5%, the next aspect of appreciating achievement (X6) 0.698 or equal to 69.8%, the honest aspect (X1) is 0.590 or 59%, the independent aspect (X5) is 0.473 or 47.3%, and the last is the creative aspect (X4) is 0.377 or 37.7%. Each partially every aspect of the character education variable contributes directly to student achievement motivation. 2). The most dominant indicator in shaping the achievement motivation of MAN Boarding School students in Aceh province is full consideration of 0.754 and the indicator of liking feedback is 0.750, meaning that the contribution given by these two indicators is in the strong category. The considerate attitude depicted by the MAN Boarding School students in Aceh province is to work on assignments carefully, meaning that every task given by the teacher will be carried out with full accuracy and re-check before the assignments are collected 3). The results of the analysis of the influence of character education on achievement motivation directly do not show a strong correlation, the resulting correlation value is 0.226 when compared to the correlation coefficient value, it can be categorized in a weak relationship or influence, but if viewed based on the aspects of forming character education, each aspect forming character education variable has a strong influence.